Marine Propellers and Propulsion (2nd Edition) - Carlton, J. S. (Elsevier, 2007)
This book fulfills the need for a comprehensive and cutting edge volume that brings together a great range of knowledge on propulsion technology, a multi-disciplinary and international subject. The book comprises three main sections covering hydrodynamics; materials and mechanical considerations; and design, operation and performance. The discussion relates theory to practical problems of design, analysis and operational economy, and is supported by extensive design information, operational detail and tabulated data. Fully updated and revised to cover the latest advances in the field, the new edition now also includes four new chapters on azimuthing and podded propulsors, propeller-rudder interaction, high-speed propellers, and propeller-ice interaction. This is a valuable reference for marine engineers and naval architects gathering together the subject of propulsion technology, in both theory and practice, over the last forty years. This is written by a leading expert on propeller technology, essential for students of propulsion and hydrodynamics.